2020
DOI: 10.3390/foods9091161
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sunlight Exposure on Anthocyanin and Non-Anthocyanin Phenolic Levels in Pomegranate Juices by High Resolution Mass Spectrometry Approach

Abstract: Quali-quantitative analyses of anthocyanins and non-anthocyanin phenolic compounds performed with the use of liquid chromatography coupled with high resolution mass spectrometry, were evaluated in juice of pomegranate fruits (‘Dente di Cavallo’), in relation to different light exposures (North, South, West and East). A total of 16 compounds were identified, including phenolic acids, flavonoids, hydrolysable tannins, and anthocyanins, known for their health-promoting effects. Striking differences were observed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 46 publications
1
12
0
Order By: Relevance
“…Di Stefano et al. reported the effects of sun exposure on anthocyanin and non‐anthocyanin phenolic levels in pomegranate juices [31] . The results revealed that significantly higher anthocyanin content was found in juices with South and North exposure, while reduced concentration of flavonoids and phenolics in fruits exposed to sun radiation in South, East, and West positions.…”
Section: Variation Of Anthocyanins In Pomegranatementioning
confidence: 99%
See 2 more Smart Citations
“…Di Stefano et al. reported the effects of sun exposure on anthocyanin and non‐anthocyanin phenolic levels in pomegranate juices [31] . The results revealed that significantly higher anthocyanin content was found in juices with South and North exposure, while reduced concentration of flavonoids and phenolics in fruits exposed to sun radiation in South, East, and West positions.…”
Section: Variation Of Anthocyanins In Pomegranatementioning
confidence: 99%
“…The results revealed that significantly higher anthocyanin content was found in juices with South and North exposure, while reduced concentration of flavonoids and phenolics in fruits exposed to sun radiation in South, East, and West positions. Hence, the authors suggested that collecting fruits with different solar exposure could obtain different health benefits of fruit juice [31] …”
Section: Variation Of Anthocyanins In Pomegranatementioning
confidence: 99%
See 1 more Smart Citation
“…This Special Issue addresses the biological activity of dietary phytochemicals, either purified [ 2 ] or in extracts from plant foods, and speculates on their potential effects on human health. The studied plant foods include edible parts (fruits, seeds, leaves, and flowers) of plants common in the Mediterranean area, such as pomegranate ( Punica granatum ) [ 3 ], oregano ( Origanum vulgare) [ 4 ], and purslane ( Portulaca olearacea ) [ 5 ], but also of several tropical plants, including annona ( Annona cherymola ) [ 6 ], herba mate ( Ilex paraguariensis ), guaranà ( Paullinia cupana ) [ 7 ], and ash gourd ( Benincasa hispida ) [ 8 ]. Bioactivity was studied in terms of radical scavenging and antioxidant [ 5 , 6 , 7 , 9 ], antimicrobial [ 10 ], and antiproliferative activity [ 4 ].…”
mentioning
confidence: 99%
“…granatum) [3], oregano (Origanum vulgare) [4], and purslane (Portulaca olearacea) [5], but also of several tropical plants, including annona (Annona cherymola) [6], herba mate (Ilex paraguariensis), guaranà (Paullinia cupana) [7], and ash gourd (Benincasa hispida) [8]. Bioactivity was studied in terms of radical scavenging and antioxidant [5][6][7]9], antimicrobial [10], and antiproliferative activity [4].…”
mentioning
confidence: 99%